Worst Law School Advice Ever - Michael A. Kahn (Washington University Journal of Law & Policy, 2017)
This Essay reflects upon multiple pieces of advice Kahn encountered while in law school. The author kindly rejects early advice he received—dubbed the “worst law school advice ever”—and affirms another—suggesting that a narrow course of study in law school may strengthen a student’s knowledge of a specific area of the law, but can limit the understanding of the law as in operates in whole. Kahn provides his own advice, suggesting instead a broad course of study that can prepare a future attorney to better deal with the rapid speed at which any given field of law can, and will, change.
Keywords: law school; law students; legal education; legal profession